Woodlawn revitalised by DHEM. Issue 1 (1st December 2018) - Hine, Kate; Von Perger, David
Abstract : This paper presents the critical and thought-provoking role DHEM has played in revitalizing the Woodlawn mine. Woodlawn, a well-known volcanic massive sulphide deposit in New South Wales, had been dormant since mine closure in 1998. Attempts to reopen the mine were stymied by a lack of lower-cost mineral resources which in turn was a function of budgetary constraints of the then-owners and the perception that new reserves would only be found at +700m depth. DHEM surveys had been little used since the 1990's due to a widespread view that the mineralization was poorly suited to EM. Despite this preconception, a deep exploration hole was approved for DHEM in 2012 and, importantly, that the entire length of hole would be surveyed 'just in case'. The result was a large off-hole conductor recorded in the upper portion of the survey, in an area considered sterilised by previous drilling. The resultant high grade and relatively shallow (300m below surface), discovery of the 1Mt 'Kate Lens', as well as several subsequent discoveries, many using DHEM, means that Woodlawn is now on track to reopen in 2018/19. This case study illustrates the importance of the 'never assume' approach to exploration, as well as the value that DHEM can add to exploration projects.